Análisis Financiero del rubro cuentas por cobrar del Comercial “Regulito” en el periodo 2019-2020. - Jiménez Alejandro, Nelson Darío (2022)
This case study takes place in the Regulito commercial to analyze the accounts receivable item in the midst of the economic risk generated by the COVID 19 virus for all economic sectors, up to a global expansion, making a comparison of the 2020 period with 2019 by the fluctuations that are observed in the first instance, looking for the origin of this alteration, considering the importance of this account because it belongs to current assets and maintains a healthy cash flow. Accounts receivable is an item that is fed, in addition to the vote of confidence, by the fact of knowing that granting credit to customers generates greater breadth in the market compared to the competition, increases sales and therefore the exit of stocks, opening the door to renewal. the good or service offered in this case by the Regulito commercial, which is the purchase and sale of rice, its derivatives and soybeans, improving the economy. With the information provided, the present study is facilitated, observing the interest of the owner, the balance sheet was used as a tool that provides reliable accounting information of the company to apply it to a horizontal analysis that showed the variation of 99.83%, a vertical analysis with values of important alteration, likewise, the values of the general balance are extracted to carry out current liquidity indices, acid test and accounts receivable turnover, average collection period, in which the response of the problem is evidenced by which This analysis began and this is the lack of resources for the proper application of a good credit system due to the economic downturn caused by covid-19.